Covid-19: Undoing our "normal" to find our humanity - Davids, N. (South African Journal of Higher Education, 2021)
At the time of writing this article South Africa has entered yet another hard lockdown, casting darkening shadows over, if not a hopeful return to “normal”, then at least to the establishment of a “new normal”. Clearly, even amid the unpredictability and trauma of a virus which strikes in an undifferentiated way across race, class, age, and geopolitical contexts, there should be nagging suspicions about a forward-looking narrative which relies on a repeated reference to “a normal”. In the case of the educational institutions, a “new normal” is embodied in virtual spaces of teaching and learning. Seemingly, objectives of embarking on a “new normal” have scant regard for the myriad existing inequities, which continue to render South African educational institutions into categories of either historical advantage, or historical disadvantage. Seemingly too, a “new normal” chooses to disregard the reality that if educational institutions are not on an equal footing, then why is there an uncritical presumption that learners and students, or teachers, for that matter, are able to access and participate in virtual learning in parity? It is a big enough challenge for most learners and students to actively participate in educational settings, when one considers the dismal living conditions of the majority of South Africans. For many of these learners and students, educational settings, even in their poor infrastructural states, represent an escape and haven from the hardships of a life entrenched in poverty. What happens when the expectation of learning shifts entirely to the capacity of the home to become a space of learning? Can we, therefore, continue to speak of a “new normal” when it is evident that there is no “normal”, not in our educational institutions, and not in our citizenship?